Testing the Efficient market Hypothesis on Weak and Semi-Strong form in the Indonesian Stock market - Rizkianto, Gita Denaya; Surya, Budhi Arta (Journal of Business and Management, 2014)
The author tested the efficient market hypothesis on the Indonesian stock market by employing the serial correlation test to test the efficient market hypothesis on weak form level and the Multifactor Arbitrage Pricing Theory (Multifactor APT) to test the efficient market hypothesis on semi-strong form level. For the test on the semi-strong form, the author chose 8 stocks with the highest market capitalization from 8 different sectors of the LQ45 index as the dependent variables and the JCI (Jakarta Composite Index), oil price, inflation rate, and the foreign exchange rate as the independent variables. The author has 2 purposes in this final project. The first purpose is to test whether the Indonesian stock market is efficient on both weak form level of efficiency and semi-strong form level of efficiency. The second purpose is to give recommendation to investors in analyzing the Indonesian stock market. The results of this final project show that the Indonesian stock market is not weak form efficient and it is not semi-strong form efficient. This means that investors can gain abnormal returns by doing technical analysis on the historical movements and fundamental analysis. Although individually the JCI, oil price, inflation rate, and foreign exchange rate have low predictive power, they collectively possess predictive power over the stock return in the Indonesian stock market. Key words: Efficient market hypothesis, weak form, semi-strong form, predictive power